Corrosion behaviour of detonation gun sprayed cermet coatings on AA5083. (1st February 2021) - Arunnellaiappan, T.; Baskaran, S.; Arun, S.; Prithivirajan, R.
ABSTRACT: Cermet coatings were fabricated on AA5083 by D gun coating technique using three different combinations of powder feedstock namely WC–Co, WC–Co–Cr, and Cr3 C2 –NiCr. The effect of powder combinations on coatings' phase composition, surface morphology, and cross-sectional microstructure were investigated using XRD, SEM, and EDS. Major findings revealed that WC–Co and WC–Co–Cr powders produced higher thickness with considerable surface defects compared to a coating that was produced by Cr3 C2 –NiCr powders. Moreover, a smooth compact and a uniform coating was obtained by using Cr3 C2 –NiCr powders. Electrochemical corrosion results showed that the OCP values of all the coated samples were shifted to a higher value than substrate and sample coated with Cr3 C2 –NiCr powder showed a stable OCP and more positive value than other coated samples. Similarly, the PDP curve of sample coated with Cr3 C2 –NiCr also showed lower corrosion current density at the cathodic region and better passivation behaviour in the anodic region.